STRATEGI MERGER PADA ERA KRISIS: ASPEK SINERGI JEJARING BISNIS - Liliana Inggrit Wijaya (Journal of Management and Business, 2006)
Globalization is a great challenging for the countries that still hard effort against economic crises. Requirement to be professional for facing competition is an absolute factor, but in the other hand they didn't find the solution way to be surviving out from the crises. In the middle of 1997, it was the beginning Indonesian crises and also the impact of the crises is still continuing until now. Gross Domestic Income in the 1998 slightly goes down 59% if comparing with the beginning of 1997, similarly for the inflation rate and Rp/US$ exchange rate slight}/goes up to 76% and 255%, whereas the condition didn't yet recovery until 2002. Economic crises affects directly the corporate performance, as written in Bisnis Indonesia (1998): economic crises is driven by monetary crises in the middle of previous year (1997) had been cutting performance of both private and public corporate with very dramatically.With the condition like that, very difficult for company to survive even still little number can, but by the fact looked that many company have been collapsed or delisted. Therefore, they must be done immediately to become efficient by consolidation through merger as a strategic step to maintenance their firm value. The target of merger is obtaining the synergy in term of the competitive advantage and strengthening to survive. From 1997 to 2002 was listed 38 public firms which had acted merger activities included horizontal (same business line), vertical (supplier and customer), congeneric (different business line but m the same industry) and conglomerate diversification (unrelated business). These merger are spread in the many kinds of sectors and the most are in the consumer goods sector as 9 companies, and the least is in the Agriculture sector, only one.The result of this research proved that the strategic ways of merger have significant positive relationship toward firm value, in the other words the financial performance after merger is greater than before. If the financed of these merger by equity (79.5%), the effect is greater than financed by debt instrument (61.6%).